Rhythm and blues: influence of CLOCK T3111C on peripheral electrophysiological indicators of negative affective processing - Armbruster, Diana; Brocke, Burkhard; Kirschbaum, Clemens; Witt, Stephanie; Lesch, Klaus-Peter J.; Strobel, Alexander (Physiology & behavior, 2020)
Dysfunction in the circadian system has been linked to emotion regulation and mood disorders with genetic variation in clock genes as likely contributors. Here, we focused on endophenotypes of affective processing and investigated in two independent samples of healthy individuals (n1=99, n2=108) whether genotypes of a functional single nucleotide polymorphism (SNP) in the gene encoding CLOCK (CLOCK T3111C, rs1801260) differed in physiological responses to emotional stimuli. Both samples underwent an emotional startle paradigm with startle responses being measured via EMG. In the second sample, skin conductance responses as well as corrugator and zygomaticus activity were also assessed. In both samples, CLOCK T3111C was associated with overall startle responses to loud noise bursts with T/T homozygotes showing consistently more marked responses. However, in the all-female second sample, the effects of CLOCK on skin conductance responses to the same loud noise bursts depended on hormone status: similar to the startle results, in free-cycling women T/T homozygotes showed more pronounced skin conductance response (SCR) compared to C allele carriers. The opposite was true for women using combined oral contraceptives (COC). A further CLOCK × hormone status interaction effect was found for corrugator activity. In free-cycling women, T/T homozygotes presented with less corrugator activity to affective pictures compared to C allele carriers, while the opposite pattern emerged for COC users. The findings emphasize the potential role of CLOCK for affect and mood.
Gesehen am 12.01.2021